External setting di kawasan Pasifik Selatan sebagai tantangan politik luar negeri Indonesia era pemerintahan Joko Widodo (2014-2023): External settings in the South Pacific region as a challenge for Indonesian foreign policy in the Joko Widodo government era (2014-2023) - Kadek Ari Sudana (JOURNAL OF GOVERNMENT SCIENCE, 2024)
The South Pacific region is an area that neighbors and directly borders Indonesia via Papua New Guinea. Members from the South Pacific are Papua New Guinea, Solomon Islands, Vanuatu, Fiji and Kanak which represents New Caledonia. Geopolitically, this area is very important for Indonesia because it is a neighbor and has a direct border. Especially in 2015 the regional organization Melanesian Spearhead Group (MSG) accepted the United Liberation Movement for West Papua (ULMWP), which is part of the Free Papua Organization, to become an observer member of the MSG. This research aims to examine challenges Indonesia's foreign policy in the South Pacific region during the President Joko Widodo (2014-2022). Qualitative research and descriptive Analysis methods that researchers use for this research use the concept of external situations and conditions (external settings) in the study of foreign policy. The results of this research are the first and main challenge, namely the development of the Papua issue in MSG and there is support from Vanuatu, inconsistent support from PNG and the Solomon Islands. Secondly, the Papua issue is also discussed at the civil society level such as Non-Governmental Organizations (NGOs), journalists, churc council, activists and students. Thirdly, The South Pacific region is not dependent on Indonesia because economic relations and cooperation between Indonesia and the South Pacific region are very small